The Effect of Using The Herringbone and Semantic Mapping Techniques on Students’ Reading Comprehension Skills at SMA Yadika Torganda - Sondang Manik; Yinghuei Chen; Lastri Wahyuni Manurung; Dewi Maya Manurung; Eliana Sitompul (Sean Institute, 2022)
This research presents a research report on the use of Herringbone Technique and Semantic Mapping Technique for students’ reading comprehension skills at SMA YADIKA Torganda. The objective is to find out the effect of using the Herringbone Technique and Semantic Mapping Technique on students’ reading comprehension skills. It was by using classroom action research. The subjects of this study were grade X students of SMA YADIKA Torganda. In this study, the writers took 90 students of SMA YADIKA Torganda as the sample. They were divided into three groups. The first and the second groups are (Experimental Groups). They were taught by using Herringbone Technique and Semantic Mapping Technique in reading recount text, while the third group (Control Group) was taught without using Herringbone Technique and Semantic Mapping Technique. The technique for data analysis is quantitative research. In analyzing the data the mean of the students’ score for pre-test in experimental group one (Herringbone Technique) is 59,16 the mean of the students’ score for post-test in experimental group one is 91,83. The mean of students’ scores for pre-test in experimental group two (Semantic Mapping Technique) is 45 the mean of the students’ score for post-test in experimental group two is 69,26. The mean for pre-test in the control group is 46,66 and the mean for post-test in the control group is 56,16. The conclusion is that the use of the Herringbone Technique and Semantic Mapping Technique significantly affect on students’ reading comprehension skills. The Herringbone technique is the most effective one in teaching recount text than the Semantic Mapping Technique It is suggested that teachers should apply this technique as one technique to improve students’ comprehension in reading recount text.